i.CREATE A SOFTWARE DEMO PRESENTATION THAT WOWS PROSPECTS: 5 MISTAKES TO AVOID ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2025)
This paper explores the key elements of delivering an effective software demo presentation and highlights five critical mistakes that often hinder success. A well-crafted demo can be the turning point in converting prospects into customers, especially in competitive markets.